The study of variations in lipid profile and GLP-1 enzyme levels of obese in sample of Iraqi population - N. J. Al-Darrji, Mustafa; F. Shehab, Adil; Y. Yaseen, Nahi; M. Karim, Rafid (Iraqi Journal of Science, 2023)
The present study conducted on 120 males obese and 50 healthy males, their ageranged from 20-50 years. The patients were divided into 3 groups based on BodyMass Index (BMI) and Central Obesity (CO.); it has noticed that there is asignificant relation between both indexes. Effect of the obesity on the lipid profilewas investigated, the results showed that there is an elevated in TG, TC, LDL-C,VLDL-C and lowered in HDL-C for all three obesity groups compare with controlgroup. Also, Significant differences (P≤0.05) revealed in TG, TC, LDL-C andVLDL-C among three obesity groups and the greatest differences recorded in groupIII obesity (279.52±1.10, 261.02±1.13, 169.32±1.81, and 55.08±1.33 mg/dlrespectively) followed by group II obesity (216.58±1.79, 228.20±1.28, 135.41±1.21and 40.34±1.17 mg/dl respectively) and then group I obesity (152.00±1.81,168.47±1.11, 104.33±1.99 and 27.90±1.46 mg/dl respectively). No significantdifferences observed in HDL-C among groups I, II and III obesity (34.23±1.59,36.65±1.78, 35.08±1.12 mg/dl respectively). The study included investigate forserum GLP-1 enzyme levels, a lowered in GLP-1 levels was observed in groups I, IIand III obesity (39.33±1.31, 35.58±1.87, 35.56±1.66 pM respectively) compare withcontrol (62.50±1.50 pM). Besides having a highly significant correlation (P≤0.01)between GLP-1 level and both indexes (BMI and CO.) in which an elevated in BMIand CO. were correlated to an lowered in GLP-1 level.